The incentive effects of affirmative action in a real-effort tournament - Calsamiglia, Caterina; Franke, Jörg; Rey-Biel, Pedro (Journal of public economics, 2013)
Affirmative action policies bias tournament rules in order to provide equal opportunities to a group of competitors who have a disadvantage they cannot be held responsible for. Its implementation affects the underlying incentive structure which might induce lower performance by participants, and additionally result in a selected pool of tournament winners that is less efficient. In this paper, we study the empirical validity of such concerns in a case where the disadvantage affects capacities to compete. We conducted real-effort tournaments between pairs of children from two similar schools who systematically differed in how much training they received ex-ante on the task at hand. Contrary to the expressed concerns, our results show that the implementation of affirmative action did not result in a significant performance loss for either advantaged or disadvantaged subjects; instead it rather enhanced the performance for a large group of participants. Moreover, affirmative action resulted in a more equitable tournament winner pool where half of the selected tournament winners came from the originally disadvantaged group. Hence, the negative selection effects due to the biased tournament rules were (at least partially) offset by performance enhancing incentive effects. ► Implementation of affirmative action (AA) might affect incentives in competition. ► Incentive effects of AA analyzed in real‐effort tournament among school children ► Experimental design relies on systematic differences in previous task experience (solving sudokus). ► No evidence for negative performance incentives due to implementation of AA ► Negative selection effects (at least partially) offset by positive incentive effects